UTILIZATION OF DIGITAL APPLICATIONS IN IMPROVING STUDENT UNDERSTANDING OF ISLAMIC RELIGIOUS EDUCATION SUBJECTS - Mustakim, Adam; Sahlan, Moh.; Saihan, Saihan; Zainudin, Agus (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
The utilization of digital technology in education continues to grow, including in learning Islamic Religious Education (PAI). This study aims to analyze the effectiveness of digital applications in improving students' understanding of PAI materials. The research was conducted through quantitative and qualitative approaches involving students and teachers from various levels of education. The results showed that digital applications, such as learning videos, interactive quizzes, and online modules, are able to improve students' understanding of Islamic concepts. However, this effectiveness depends on device availability, digital literacy and teacher support. This study suggests the integration of digital apps designed according to the curriculum and students' needs.